Green Entrepreneurship as a Catalyst for Circular-Local Economic Development and Environmental Protection - Kusaimah Kusaimah; Iwil Suprianto; Febrian Chandra; Atron Atron (Lembaga Riset Ilmiah, 2026)
Economic growth based on linear production patterns has created serious pressure on environmental sustainability. This article analyzes the role of green entrepreneurship as a driver of local economic development and as an instrument of environmental conservation within the ecosystem of micro, small and medium enterprises (MSMEs). This study uses a descriptive qualitative method through literature review, policy-document analysis, and conceptual synthesis of the circular economy and MSME financing. The synthesis was conducted by juxtaposing circular economy principles with local supply chain dynamics to construct a novel theoretical framework tailored specifically for small-scale enterprises. The findings show that green entrepreneurship can strengthen local supply chains, create green jobs, improve resource efficiency, expand access to sustainable financing, and connect local community-based businesses with environmentally conscious markets. However, the transition of MSMEs toward green practices still faces barriers, including low environmental literacy, limited clean technology, restricted access to green finance, and uneven certification assistance. The novelty of this article lies in the formulation of the Circular-Local Green MSME Ecosystem. Theoretically, this framework shifts the paradigm of MSMEs from passive beneficiaries of development programs to proactive, community-based agents of ecological preservation. Practically, it offers policymakers a grounded model to design targeted green financing and capacity-building interventions that align environmental sustainability with local competitiveness.